35. IMPACT OF AGRICULTURAL INJURIES ON FARMERS IN THAI BINH IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the impact of agricultural injuries on farmers in Thai Binh in 2024.Methods: A descriptive cross-sectional study was conducted in 2413 farmers.Results: The rate of injury in farmers accounted for 17%; there were 11.23 ± 21.69 days off work on average; the durations of time that those individuals required assistance with personal and daily activities were 3.83 ± 9.44 days and 5.20 ± 11.98 days, respectively. For agricultural laborers, the average cost covered injury treatment was 1029.37 ± 2861.83 thousand Vietnam dong. 11.2% had major impacts on their household economy after the injuries.Conclusion: Farmers’ health and financial situation are greatly impacted by accidents that occur while they are working in agriculture. In order to lessen the burden of agricultural injuries on farmers, more studies or suitable solutions are required.
Keywords: Agricultural workers, accidents injuries, impacts, Thai Binh.